Promoting collaborative practice and reciprocity in initial teacher education: realising a ‘dialogic space’ through video capture analysis - Youens, Bernadette; Smethem, Lindsey; Sullivan, Stefanie (Taylor & Francis, 2014)
This paper explores the potential of video capture to generate a collaborative space for teacher preparation; a space in which traditional hierarchies and boundaries between actors (student teacher, school mentor and university tutor) and knowledge (academic, professional and practical) are disrupted. The study, based in a teacher education department in an English university, is contextualised in the policy context of school–university partnerships. Video capture is used as a vehicle to promote dialogue and collaborative practice between partners during school-based elements of a teacher preparation course. Analysis highlights the power of this space to promote reciprocal learning across the partnership.